Analysis of the current status and influencing factors of kinesiophobia in tumor patients with peripherally inserted central catheter: A cross-sectional study - Xiaohua Zhu; Yan Wu; Rong Li; Xiaozhu Qiao; Ying Yang; Fang Chen (PLoS ONE, 2026)
Background Peripherally Inserted Central Catheters (PICCs) are widely utilized in tumor patients due to their lower risk of complications, extended indwelling duration, reduced local tissue trauma, and overall cost-effectiveness. Based on the Health Action Process Approach (HAPA) theory, this study aims to explore the current status and influencing factors of kinesiophobia in tumor patients with PICCs. The study provides reference for clarifying the mechanism of kinesiophobia and developing nursing intervention plans. Method Through convenience sampling, 162 tumor patients who underwent PICC maintenance in three hospitals in Jiangsu Province from December 4th, 2023, to December 31st, 2024 were selected. The patient general information questionnaire, Tampa scale of kinesiophobia, medical coping modes questionnaire, exercise self-efficacy scale, risk perception questionnaire, outcome expectation scale, exercise intention scale, and social support rating scale were used for evaluation. Result Tumor patients carrying PICC had a kinesiophobia score of 20.11 ± 6.94 points, and 42.59% of tumor patients with PICC had kinesiophobia. The results of multiple linear regression showed that the duration of catheter placement(t = −3.506,P = 0.001), pain(t = 2.652,P = 0.009), exercise self-efficacy(t = −3.891,P < 0.001), and risk perception(t = 3.157,P = 0.002) are the main influencing factors of kinesiophobia in tumor patients with PICC. Conclusion The findings underscore a significant clinical concern regarding kinesiophobia among tumor patients with PICC. It is essential for nursing staff to implement systematic assessments and tailored interventions aimed at mitigating kinesiophobia. Addressing this issue can contribute to reducing associated adverse reactions and improving patient mobility and overall quality of life.